Unusual molecular orientation and frozen librational motion of C60 on Cu(110) - Fasel, R.; Agostino, R. G.; Aebi, Philipp; Schlapbach, Louis (My University, 1999)
Full-hemispherical angle-scanned x-ray photoelectron diffraction has been used to investigate the molecular orientation and librational motion of C60 molecules adsorbed on the Cu(110) surface. The molecules are found to face the substrate surface in an unusual bonding configuration, rotating their symmetry axes by a few degrees away from the high-symmetry directions of the Cu(110) substrate. Despite the asymmetric molecular orientation, the C60 molecules are immobile, i.e., they show no librational motion, up to temperatures well above the C60 sublimation temperature.